Technology and Curriculum: Shadows and Machines - Lewkowich, David (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2012)
The influence of technology in today’s classroom is undeniably ubiquitous and scattered, and though the practice of conceptualizing technological application emerges from within an already contested and highly politicized field of human relations, when approached in the context of curriculum, this contestation takes on new significance. In this paper, I construct a claim that, when introduced into the sphere of education, technology brings its own curricular shadows. I argue that while certain technologies seem to place restrictions on a learner’s capacity for expression and experimentation, these restrictions are by no means absolute or immovable, and that to think through technology aesthetically is to posit the presence of alternative possibilities and meanings. The performative potential of technology is here considered as within a dialogue with the curriculum-as-lived-experience, where learning necessarily exclaims its ambiguity as a forever-fluctuating relationality.